(untitled) (Journal of Agriculture and Plant Sciences, 2013)
Examination of traits vegetation length, genetic potential for brain and possibilities for breeding of the genotype hybrid maize from the maturity group of FAO 580, GS – 308 (with origin from Israel), studied in 2004 in Pelagonia, the vicinity of Bitola, with and without irrigation. Despite the late sowing of this genotype, the trait vegetation length showed positive results, the vegetation was successfully fi nished in three locations, and the genetic potential yielded quite good brain. The trait length of vegetation of the FAO 580 genotype hybrid maize is 130 days, but the vegetation length of the examined Israeli hybrid GS -308 is 139-149 days which means that the vegetation period is 9-19 days longer as a result of late sowing and the impact of climate conditions (t oC and rainfalls) which were an exception this year of examination. The trait genetic potential for brain was most evident in the village Novaci (9.400 kg/ha) with 29.5% grain moisture during harvest, followed by the village Egri (9.200 kg/ha) with 29.9% grain moisture during harvest. The trait was least evident in the village Mogila (7.350 kg/ha) with 32% grain moisture during harvest. As a result of late sowing and breeding without irrigation. The genetic potential for brain of the GS-308 genotype hybrid corn has been manifested successfully despite late sowing. The hybrid can be bred with success in Pelagonia, the vicinity of Bitola and other country regions up to 600 m height above the sea level.